Influência do ângulo de posição sobre o fresamento frontal de níquel puro com insertos de metal duro - Marcelo Araujo Camara (2008)
Nickel is considered as a dificult-to-cut material, due to rapidly work hardening when machined. Because it shows high strength at high temperatures it is widely used as high temperature alloys in aerospacial components and more specifically is applied in the continuous casting industry, in molds which consist of a copper sheet with pure nickelelectroplated, mounted over steel boxes, at the beginning of continuous cast process. The molten steel is poured into the tundish, then is driven to molds box, which must support the wear caused by steel sliding at high temperature. The principal aim of this work is to investigate the influence of the side cutting edge angle r on the cutting forces, wearmechanisms, surface finish and metal removal rate during face milling of pure nickel. Three types of milling cutters were used, with r = 12°, 45° e 90, and keeping the cut thickness constant equal to 0,25 mm. The tests compared: milling cutters with r = 90° and 45°, DOC = 1,0 mm, milling cutter with r = 45° at different cutting speed and milling cutters with r = 45° and 12°, DOC = 0,5 mm. The results indicated the milling cutter with r = 12° was superior with regard to metal removal rate and higher cutting forces, while the milling cutter with r = 45° was superior regard to tool life and smaller values to surface finish Rz. Beside the influence of the side cutting edge angle r, the effect of tools coating and the cutting speed were investigated, showing longer tool life to insert coated with TiN-Al2O3-TiCN (CVD) compared to TiAlN (PVD) coating when used milling cutter with r = 12°, and bigger growing rate of crater wear at bigger surface speed when used milling cutter with r = 45°.